Influence of the Competency, Independency, Accountability and Audit Firm Size on Audit Quality - Annisa Rahmawati; Dian Agustia; Yustrida Bernawati (AKRUAL: JURNAL AKUNTANSI, 2019)
Audited financial statement was an assurance for users of financial statement for the reliability of the information they use for making business decisions. Therefore, this study was intended to empirically examine the effect of competence, independence, accountability, and size of public accounting firms on audit quality. the hypothesis to was tested Structural Equation Modeling (SEM), which makes it possible to measure latent variables and hypothesis testing simultaneously. The result showed that competence had a positive impact on audit quality. Meanwhile, independency, accountability and audit firm size do not support the hypothesis.